Republic of Moldova : Selected Issues. (IMF Staff Country Reports; Country Report, 2020)
This Selected Issues paper provides a systematic assessment of Moldova's governance and institutional frameworks. It follows guidelines approved by the IMF executive board, which were developed to deliver systematic and even-handed analysis on macroeconomically critical governance and institutional vulnerabilities. This paper also focuses on seven key areas for IMF engagement: corruption, rule of law, regulatory framework, fiscal governance, financial sector oversight, anti-money laundering/combating the financing of terrorism, and central bank governance. The analysis is based on internationally comparable data, diagnosis from IMF technical assistance reports, as well as other expert assessments. Strengthening the judiciary and rule of law and accelerating state-owned enterprises (SOE) reform are clear priorities. The widespread nature of governance vulnerabilities and institutional weaknesses in Moldova, combined with capacity constraints, creates challenges for policy formulation and prioritization. Policy efforts should therefore focus on strengthening rule of law and reforming Moldova's judiciary system, as well as building capacity and increasing the autonomy of key institutions. Steadfast SOE reform would foster competition, investment, and productivity, while reducing fiscal risks.